Influence of the Me2SO removal on key parameters of cryopreserved autologous peripheral progenitor cells concentrates: a retrospective study in patients with primary or secondary amyloidosis - Jandová , Miroslava; Měřička, Pavel; Gregor, Jiří; Lánská, Miriam; Vokurková, Doris; Fátorová, Ilona; Bezrouk, Aleš; Radocha, Jakub (Problems of Cryobiology and Cryomedicine, 2022)
Probl Cryobiol Cryomed 2022; 32(4):298